Influência do álcool na adesão à terapia antirretroviral e na qualidade de vida de pessoas vivendo com HIV/AIDS - Santos, Vanessa da Frota (2015)
The purpose of the study was to analyze the influence of alcohol on adherence to antiretroviral therapy and quality of life of people living with HIV / AIDS (PLWHA). It is a cross-sectional study, developed in the clinic of infectious diseases at the University Hospital Walter Cantídio (HUWC) of the Federal University of Ceará (UFC). The sample consisted of 114 PLWHA, of both sexes, aged ≥ 18 years in use of antiretroviral therapy for more than two months. Structured interview evaluated the sociodemographic characteristics and clinic. To evaluate the quality of People Living with HIV / AIDS was used the WHOQOL-HIV BREF, they have also used the test to evaluate the alcohol consumption mode (AUDIT) and the Questionnaire for the Assessment of Adherence to Antiretroviral Treatment (CEAT-VIH). Statistical analysis is used the tests: Mann-Whitney, Odds Ratio and Fisher. Prevalence ratio, mean, standard deviation, median, minimum and maximum values were calculated when needed. It was considered statistically significant P value <0,05. The softaware Statistical Package for the Social Sciences (SPSS) version 20.0 for analysis. Results show, most patients were male (54.3%), brown (53.5%), with up to complete high level (61.4%), married / with partner (45.6%), employed (52.6%), and religion (92.9%) with mean age of 18-39 years (48.2%). Predominant heterosexual exposure (74.5%), and 50.8% lived with a partner. The most commonly used antiretroviral was a lamivudina (85.9%). Among them was 55.2% with no history of alcohol and other illicit drugs (80.7%). Most (89.4%) with low risk for alcohol use. Among patients at high risk for alcohol consumption (10.5%) there was significant compared with previous history of alcohol use (Odds Ratio: 4.29; p-value: 0.03) and no history of illegal drugs (Odds Ratio: 3.57; p-value: 0.04) .In relation to adherence to ART, 63.1% of patients had adequate / good adhesion, were not found significant amounts of alcohol and adherence to ART. He was found impairment in quality of life by areas: Independence level (15.0) and Environment (15.0). PLWHA at high risk for alcohol consumption have lower scores on Physical domains (p = 0.01) and social relations (p = 0.01). We conclude that the use of high risk PLWHA negative impact on the Quality of Life.